A wind in the door [compact disc, unabridged] - L'Engle, Madeleine (L'Engle, Madeleine. Time quintet., 2012)
With Meg Murry's help, the dragons her six-year-old brother saw in the vegetable garden play an important part in his struggle between life and death.